Photodegradation catalyst prepared from saccharide hydrolysis by-product humus and method and application of photodegradation catalyst
By combining the byproduct of carbohydrate hydrolysis humus with photocatalytic technology, photodegradation catalysts are prepared, which solves the problem of difficult to eliminate humins in the production of high-value chemicals for biomass, and achieves the effect of efficient degradation of organic dyes and improving waste utilization.
Patent Information
- Application Number
- CN202411679921.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-04
AI Technical Summary
In the production process of high-value biomass chemicals, by-product humins are difficult to eliminate, resulting in increased marginal costs and decreased profits, hindering industrial production.
The photodegradation catalyst is prepared by using the by-product of carbohydrate hydrolysis humus as a support, and the metal and non-metal oxides are supported, and the photodegradation reaction of organically contaminated wastewater is carried out under light.
The catalytic efficiency is improved, high-energy and high-pollution organic dyes are effectively degraded, waste utilization is improved, energy utilization is expanded, and catalyst circulation is reduced.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biomass resource utilization, and in particular to a method and application of preparing a photodegradation catalyst by utilizing humus, a byproduct of sugar hydrolysis. Background Art
[0002] In recent years, biomass-based chemicals have gradually become the focus of national attention. Carbohydrates in biomass are converted into high-value platform chemicals such as 5-HMF, LA (levulinic acid), DFF (furandicarboxaldehyde), THFDM (tetrahydrofuran dimethanol) and FDM (furan dimethanol) through a series of chemical means. These chemicals can be used to prepare pharmaceutical intermediates, fuels and polyester monomers, in order to replace traditional petroleum-based chemicals and fossil fuel energy.
[0003] However, the byproduct humins generated during the conversion process is always difficult to avoid and eliminate. Even if there are ways to reduce the generation of humins, the elimination of humins often results in the production process of biomass-based high-value chemicals failing to reach Pareto optimality, which in turn leads to increased marginal costs and reduced profits, hindering the industrial production of such high-value chemicals. Therefore, in recent years, academic research has gradually begun to use the technical route of converting humins into products as a research branch.
[0004] Humins are generally formed by cross-linking polymerization of furan, pyran, carboxyl and carbonyl groups through reactions such as aldol condensation, etherification and esterification. Therefore, the structure, viscosity, morphology and special functional groups contained are affected by the types of reaction substrates, catalytic reagents, products and process conditions, and show great differences. Due to their special structures such as possible α-unsaturated sites and oxygen-containing chromophores, humins are generally dark brown and have relatively low calorific value. They are generally difficult to dissolve in water, which adds a lot of difficulty to the cleaning of instruments and equipment. But also because of this, humins have certain chemical activity and the ability to accept free electrons, which can improve the charge distribution to a certain extent; at the same time, humins will present a loose and porous structure under certain conditions, so they can be used as catalytic active sites or catalyst carriers for chemical reactions, and assist in the catalytic degradation of complex toxic macromolecules such as organic dyes. Organic dyes usually have complex molecular structures. The classic structures of dyes include azo, anthraquinone, indigo, trityl and phthalocyanine derivatives. Most dyes are non-biodegradable, toxic and carcinogenic, which not only damage the environment but also threaten biological health, so they are extremely polluting.
[0005] Taking advantage of the special structure and chemical properties of humins, the relatively environmentally friendly photocatalytic technology is combined with waste humins generated by sugar hydrolysis, which can not only improve the catalytic efficiency, but also enable high-value applications of the humins already generated in the system; the prepared photocatalyst can effectively eliminate high-energy and highly polluting organic dyes, while rationally converting light energy into chemical energy, rationally utilizing and distributing energy, conforming to the "dual carbon" concept advocated by the country in recent years, and providing a new direction for the high-value utilization and transformation of biomass.
[0006] Therefore, the present invention aims to provide a method for preparing a photocatalyst from humus, using the byproducts of sugar hydrolysis as a carrier to degrade high-energy and high-polluting chemicals under light. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a method and application of preparing a photodegradation catalyst using humus, a by-product of carbohydrate hydrolysis, using humus generated during carbohydrate hydrolysis as a raw material, loading metal and non-metal oxides to synthesize a photocatalyst, and performing a photodegradation reaction of organic polluted wastewater in a solvent under light irradiation.
[0008] To achieve the above object, the technical solution of the present invention is as follows: The present invention proposes a method for preparing a photodegradation catalyst using humus, a byproduct of sugar hydrolysis, comprising the following steps: 1) Using sugar compounds as raw materials, mixing them in a water / organic two-phase system of an acidic catalyst, a co-catalyst, water, and an organic solvent, raising the temperature to a certain temperature and reacting for a period of time, and obtaining a crude humins carrier after treatment; 2) The crude humins carrier, the metal compound or the non-metal compound are dispersed uniformly in an organic solvent in a high temperature and high pressure reactor, and then the temperature is raised and maintained for a period of time. After the reaction is completed, the recovered solid is washed and dried to obtain a humins-based photodegradation catalyst.
[0009] Furthermore, in step 1), the carbohydrate compound includes one or more of free sugar, polysaccharide, and sugar-containing solution; the free sugar is one or more of fructose, glucose, maltose, sucrose, and inulin; the polysaccharide is cellulose or starch; the sugar-containing solution is one or more of high fructose syrup, homemade fructose-glucose syrup, and concentrated syrup; Step 1) The neutral acid catalyst is one or more of concentrated sulfuric acid, concentrated hydrochloric acid, phosphoric acid, citric acid, lactic acid, maleic acid, p-toluenesulfonic acid, formic acid, acetic acid, and aminosulfonic acid; the co-catalyst is an active metal chloride, specifically one or more of aluminum chloride, ferric chloride, chromium chloride, sodium chloride, potassium chloride, calcium chloride, and magnesium chloride; In step 1), the organic phase is selected from one or more mixed solvents selected from dimethyl carbonate, methanol, ethanol, 4-methyl-2-pentanone, dimethyl sulfoxide, N,N-dimethylformamide, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, 1-butanol, 2-butanol, γ-valerolactone, and isopropanol.
[0010] Furthermore, in step 1), the mass ratio of the sugar compound to the mass of the acidic catalyst, the mass of the co-catalyst, the volume of water, and the volume ratio of the organic solvent is 1: 0.01-0.1: 0.01-0.05: 0.2-0.8: 1.0-2.0, the volume unit is mL, and the mass unit is g; in step 1), the reaction temperature is 140-160° C., and the reaction time is 1-2 h.
[0011] Furthermore, in step 2), the metal compound is selected from one or more of TiO2, CuO, Cu2O, ZnO, Ag2O, Fe3O4, WO3, CeO2 and CdO; the non-metallic oxide is SiO2; and the organic solvent in step 2) is methanol, ethanol, isopropanol or acetone.
[0012] Furthermore, in step 2), the reaction temperature is 150-220° C., and the reaction time is 2.5-5.5 h; in step 2), the mass ratio of the crude humins carrier to the compound is 1:2-4.
[0013] The invention provides a photodegradation catalyst prepared by the method.
[0014] The invention also proposes the application of a photodegradation catalyst in the degradation of organic dyes.
[0015] Further, the following steps are included: The prepared photodegradation catalyst and organic dye are placed in a light-transmitting conical flask for reaction, and the catalyst is evenly dispersed in the organic dye by stirring. Before irradiation, stirring is performed in the dark, and then the photodegradation reaction is irradiated under light.
[0016] Furthermore, the organic dye solution is one or more of methylene blue, malachite green, methyl orange, crystal violet, Congo red and rhodamine B solution; the concentration of the organic dye solution is 10-50 mg / L, the pH value is 4-6.5, the reaction temperature is 20-40° C., and the concentration of the humins-loaded photodegradation catalyst when catalyzing dye degradation is 1-50 g / L; the illumination adopts one or more of natural light, ultraviolet xenon lamp, and ultraviolet mercury lamp.
[0017] Furthermore, the ultraviolet wavelength is 280-380 nm, and the irradiation intensity is 0.30-18 W / m 2 , the illumination time is 60~300min.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) The present invention uses a saccharide compound as a raw material, mixes it in a water / organic two-phase system of an acidic catalyst, a co-catalyst, water, and an organic solvent, raises the temperature to a certain temperature and reacts for a period of time, and then obtains a crude humins carrier after treatment. Then, the crude humins carrier and a metal oxide or a non-metallic oxide are dispersed uniformly in water in a high-temperature and high-pressure reactor, and then the temperature is raised and maintained for a period of time. After the reaction is completed, the solid recovered is washed and dried to obtain a humins-based photodegradation catalyst; 2) The photocatalytic degradation catalyst prepared by the present invention degrades organic dyes. The conversion rate of photocatalytic degradation of methylene blue by the method of the present invention can reach up to 85.36%; the conversion rate of malachite green can reach up to 87.72%; 3) Compared with traditional chemical catalysis, photocatalysis converts light energy into chemical energy, further expanding the energy utilization pathway; at the same time, the byproducts of carbohydrate hydrolysis are combined with catalysis to improve waste utilization and catalytic efficiency; compared with biocatalysis, photocatalysis can effectively degrade high-pollution and high-energy pollutants; 4) The present invention uses a method of combining humins, a byproduct of sugar hydrolysis, with photocatalytic technology to degrade organic dyes. The catalytic reaction is relatively efficient and has high energy utilization rate. At the same time, the catalytic effect of the photocatalyst decreases less after multiple cycles, providing a new way to reduce solid waste generated by biomass conversion and efficiently degrade water pollutants. DETAILED DESCRIPTION
[0019] The present invention will be further described below in conjunction with specific embodiments, but the scope of protection of the present invention is not limited to the described scope. Example 1
[0020] This embodiment provides a TiO2-loaded photodegradation catalyst, and the preparation process is as follows: 1) Weigh 40 g of glucose, 1.20 g of maleic acid, 0.40 g of ferric chloride, 50 mL of MIBK and 25 mL of deionized water, mix them, put them into a 100 mL hydrothermal reactor, stir them at room temperature for at least 0.5 h, keep them warm at 155 ° C for 1 h, cool them to room temperature, first rotary evaporate the reaction solution, then add water and filter it, crush the obtained solid particles, wash them with an appropriate amount of 1-n-butanol, and then put them into an oven at 75-80 ° C for more than 6 h to obtain a crude humins carrier; 2) Take 0.35g of humins crude carrier, 30mL of deionized water, 10mL of ethanol and 0.7g of TiO2 and put them into a 50mL micro high temperature and high pressure reactor, stir at room temperature for at least 2h, then heat to 160℃ and keep for 5h, cool to room temperature, filter and wash with deionized water, put into an oven at 75-80℃ and bake for more than 12h to obtain a photocatalyst, recorded as 1-TiO2 / Hu (160-5). Example 2
[0021] This embodiment provides a ZnO-loaded photodegradation catalyst, and the preparation process is as follows: 1) Weigh 40g of glucose, 0.40g of concentrated sulfuric acid, 0.50g of aluminum chloride, 60mL of GVL and 15mL of deionized water, mix them, put them into a 100mL hydrothermal reactor, stir them at room temperature for at least 0.5h, keep them warm at 150℃ for 2h, cool them to room temperature, first rotary evaporate the reaction liquid, then add water and filter it, crush the obtained solid particles, wash them with an appropriate amount of 2-butanol, and then put them into an oven at 75-80℃ for more than 6h to obtain a crude humins carrier; 2) Take 0.50g of humins crude carrier, 25mL of deionized water, 15mL of methanol and 1.0g of ZnO and put them into a 50mL micro high temperature and high pressure reactor, stir at room temperature for at least 2h, then heat to 180℃ and keep for 4h, cool to room temperature, filter the reaction solution and wash the recovered solid with deionized water, then put it into an oven at 75-80℃ and bake for more than 12h to obtain a photocatalyst, recorded as 2-ZnO / H (180-4). Example 3
[0022] This embodiment provides a CuO-loaded photodegradation catalyst, and the preparation process is as follows: 1) Weigh 45g of fructose syrup, 0.90g of p-toluenesulfonic acid, 1.50g of calcium chloride, 65mL of DMC and 10mL of deionized water, mix them, put them into a 100mL hydrothermal reactor, stir them at room temperature for at least 0.5h, keep them warm at 145℃ for 2.5h, cool them to room temperature, first rotary evaporate the reaction liquid, then add water and filter it, crush the obtained solid particles, wash them with an appropriate amount of 1-n-butanol, and then put them into an oven at 75-80℃ for more than 6h to obtain a crude humins carrier; 2) Take 0.30 g of the crude humins carrier, 30 mL of deionized water, 10 mL of methanol and 0.72 g of CuO and put them into a 50 mL micro high temperature and high pressure reactor. Stir at room temperature for at least 2 h, then heat to 200 °C and keep for 1 h. After cooling to room temperature, filter and wash with deionized water. Put it in an oven at 75-80 °C for more than 12 h to obtain a photocatalyst, which is recorded as 3-CuO / Hu (200-1).
[0023] Using the specific photocatalyst prepared above, experiments on photocatalytic degradation of dyes were carried out, and the examples are as follows. Example 4
[0024] This embodiment provides a method for degrading methylene blue with a photodegradation catalyst, which is carried out according to the following steps: Take 0.05 g of the photocatalyst 1-TiO2 / Hu (160-5) obtained in Preparation Example 1 and 50 mL of a methylene blue solution with a concentration of 75 mg / L and place them in a light-transmitting conical flask for reaction. Use a magnetic stirrer at a stirring speed of 800 r / min to evenly disperse the catalyst in the methylene blue solution. Stir in the dark for 30 minutes before irradiation, then turn on the ultraviolet light with a wavelength of 300 nm and an irradiation intensity of 1.35 W / m 2 The photodegradation reaction was carried out under irradiation of fluorescent ultraviolet lamp for 5 hours; the reaction was carried out at 25~30℃ and the pH was adjusted to 5.5-6.0.
[0025] After the reaction is completed, the solution is sampled and the concentration of the remaining organic dye is determined using a UV-visible spectrophotometer.
[0026] In the present application, the organic dye content is tested by UV-visible spectrophotometer, and the absorbance of methylene blue is detected at a wavelength of 665nm and that of malachite green is detected at a wavelength of 620nm, and quantified by external standard method. In the external standard method, the concentration test range of methylene blue is 2-50mg / L, and the concentration test range of malachite green is 5-50mg / L, wherein the calculation formula of the conversion rate (C) of the organic dye is as follows (the detection and calculation methods of the following embodiments are the same as those of this embodiment):
[0027] c 0 ——initial concentration of organic dye solution; c ——Concentration of organic dye solution after photodegradation, mg / L.
[0028] Calculation shows that the organic dye used in this embodiment is methylene blue, and its conversion rate (C) is 72.69%. Example 5
[0029] This embodiment provides a method for degrading methylene blue with a photodegradation catalyst, which is carried out according to the following steps: 0.05 g of the photocatalyst 2-ZnO / H (180-4) obtained in Preparation Example 2 and 50 mL of a methylene blue solution with a concentration of 75 mg / L were placed in a light-transmitting conical flask for reaction. A magnetic stirrer was used at a stirring speed of 800 r / min to uniformly disperse the catalyst in the methylene blue solution. Before irradiation, the mixture was stirred in the dark for 30 min, and then the ultraviolet light with a wavelength of 285 nm and an irradiation intensity of 0.85 W / m2 The photodegradation reaction was carried out under irradiation of fluorescent ultraviolet lamp for 3 hours; the reaction was carried out at 25~30℃ and the pH was adjusted to 5.5-6.0.
[0030] After the reaction was completed, the solution was sampled and the remaining methylene blue concentration was measured using a UV-visible photometer. The calculated conversion rate of methylene blue was 81.75%. Example 6
[0031] This embodiment provides a method for degrading methylene blue with a photodegradation catalyst, which is carried out according to the following steps: 0.04 g of the photocatalyst 3-CuO / Hu (200-1) obtained in Preparation Example 3 and 50 mL of a methylene blue solution with a concentration of 75 mg / L were placed in a light-transmitting conical flask for reaction. A magnetic stirrer was used at a stirring speed of 800 r / min to uniformly disperse the catalyst in the methylene blue solution. Before irradiation, the mixture was stirred in the dark for 30 min, and then the ultraviolet light with a wavelength of 285 nm and an irradiation intensity of 0.85 W / m 2 The photodegradation reaction was carried out under the irradiation of fluorescent ultraviolet lamp for 5 hours; the reaction was carried out at 25-30°C and the pH was adjusted between 5.5-6.0.
[0032] After the reaction was completed, the solution was sampled and the remaining methylene blue concentration was measured using a UV-visible photometer. The conversion rate of methylene blue was calculated to be 85.36%. Example 7
[0033] This embodiment provides a method for degrading malachite green using a photodegradation catalyst, which is carried out according to the following steps: Take 0.03 g of the photocatalyst 1-TiO2 / Hu (160-5) obtained in Preparation Example 1 and 50 mL of 55 mg / L malachite green solution in a light-transmitting conical flask for reaction, and use a magnetic stirrer at a stirring speed of 800 r / min to evenly disperse the catalyst in the malachite green solution; stir in the dark for 30 min before irradiation, and then turn on the ultraviolet wavelength of 285 nm and the irradiation intensity of 0.85 W / m 2 The photodegradation reaction was carried out under the irradiation of fluorescent ultraviolet lamp for 5 hours; the reaction was carried out at 25-30°C and the pH was adjusted to 4.5-5.0.
[0034] After the reaction was completed, the solution was sampled and the remaining malachite green concentration was measured using a UV-visible spectrophotometer. The malachite green conversion rate was calculated to be 81.27%. Example 8
[0035] This embodiment provides a method for degrading malachite green using a photodegradation catalyst, which is carried out according to the following steps: 0.05 g of the photocatalyst 2-ZnO / H (180-4) obtained in Preparation Example 2 and 50 mL of 55 mg / L malachite green solution were placed in a light-transmitting conical flask for reaction. A magnetic stirrer was used at a stirring speed of 800 r / min to uniformly disperse the catalyst in the malachite green solution. Before irradiation, the mixture was stirred in the dark for 30 min, and then the ultraviolet light was turned on with a wavelength of 285 nm and an irradiation intensity of 0.85 W / m 2 The photodegradation reaction was carried out under irradiation of fluorescent ultraviolet lamp for 3 hours; the reaction was carried out at 25~30℃ and the pH was adjusted to 5.5-6.
[0036] After the reaction was completed, the solution was sampled and the remaining malachite green concentration was determined using a UV-visible spectrophotometer. The calculated malachite green conversion rate was 83.15%. Example 9
[0037] This embodiment provides a method for degrading malachite green using a photodegradation catalyst, which is carried out according to the following steps: Take 0.05 g of the photocatalyst 3-CuO / Hu (200-1) obtained in Preparation Example 3 and 50 mL of 55 mg / L malachite green solution in a light-transmitting conical flask for reaction, and use a magnetic stirrer at a stirring speed of 800 r / min to evenly disperse the catalyst in the malachite green solution; stir in the dark for 30 min before irradiation, and then turn on the ultraviolet light with a wavelength of 285 nm and an irradiation intensity of 0.85 W / m 2 The photodegradation reaction was carried out under irradiation of fluorescent ultraviolet lamp for 5 hours; the reaction was carried out at 25~30℃ and the pH was adjusted to 5.5-6.
[0038] After the reaction was completed, the solution was sampled and the remaining malachite green concentration was determined using a UV-visible spectrophotometer. The calculated malachite green conversion rate was 87.72%. Example 10
[0039] The recovered catalysts 1-TiO2 / Hu (160-5), 2-ZnO / H (180-4) and 3-CuO / Hu (200-1) were used to photocatalytically degrade methylene blue in the following steps: After centrifugation, the solids of the recovered photocatalysts 1-TiO2 / Hu (160-5), 2-ZnO / H (180-4) and 3-CuO / Hu (200-1) were washed with clean water for multiple times, dried at 75°C for 8 hours, and recovered and marked as 1-TiO2 / Hu (160-5-R), 2-ZnO / H (180-4-R) and 3-CuO / Hu (200-1-R) in sequence. The conditions of Examples 4, 5, and 6 were repeated in sequence, and each catalyst was subjected to at least 5 cycle experiments. After each cycle experiment, samples were taken and tested with a UV-spectrophotometer.
[0040] Table 1: Analysis results of Example 10 Embodiment 11
[0041] The recovered catalysts 1-TiO2 / Hu (160-5), 2-ZnO / H (180-4) and 3-CuO / Hu (200-1) were used for photocatalytic degradation of malachite green in the following steps: After centrifugation, the solids of the recovered photocatalysts 1-TiO2 / Hu (160-5), 2-ZnO / H (180-4) and 3-CuO / Hu (200-1) were washed with clean water for multiple times, dried at 75°C for 8 hours, and recovered and marked as 1-TiO2 / Hu (160-5-R), 2-ZnO / H (180-4-R) and 3-CuO / Hu (200-1-R) in sequence. The conditions of Examples 4, 5, and 6 were repeated in sequence, and each catalyst was subjected to at least 5 cycle experiments. After each cycle experiment, samples were taken and tested with a UV-spectrophotometer.
[0042] Table 2: Analysis results of Example 11
[0043] The above experimental results show that the conversion rate of photocatalytic degradation of methylene blue by the method of the present invention can reach up to 85.36%; the conversion rate of malachite green can reach up to 87.72%. Compared with traditional chemical catalysis, photocatalysis converts light energy into chemical energy, further expanding the energy utilization pathway; at the same time, the byproducts of the hydrolysis of sugar compounds are combined with catalysis to improve the waste utilization rate and catalytic efficiency; compared with biocatalysis, photocatalysis can effectively degrade high-pollution and high-energy pollutants.
[0044] In summary, the present invention adopts a method of combining humins, a byproduct of sugar hydrolysis, with photocatalytic technology to degrade organic dyes. The catalytic reaction is relatively efficient and has high energy utilization rate. At the same time, the catalytic effect of the photocatalyst decreases less after multiple cycles, providing a new way to reduce solid waste generated by biomass conversion and efficiently degrade water pollutants.
Claims
1. A method for preparing a photodegradation catalyst using humus, a byproduct of sugar hydrolysis, characterized in that The steps include: 1) Using sugar compounds as raw materials, mixing them in a water / organic two-phase system of an acidic catalyst, a co-catalyst, water, and an organic solvent, raising the temperature to a certain temperature and reacting for a period of time, and obtaining a crude humins carrier after treatment; 2) The crude humins carrier, the metal compound or the non-metal compound are dispersed uniformly in an organic solvent in a high temperature and high pressure reactor, and then the temperature is raised and maintained for a period of time. After the reaction is completed, the recovered solid is washed and dried to obtain a humins-based photodegradation catalyst.
2. The method for preparing a photodegradation catalyst using humus, a byproduct of sugar hydrolysis, according to claim 1, characterized in that In step 1), the carbohydrate compound includes one or more of free sugar, polysaccharide, and sugar-containing solution; the free sugar is one or more of fructose, glucose, maltose, sucrose, and inulin; the polysaccharide is cellulose or starch; the sugar-containing solution is one or more of high fructose syrup, homemade fructose-glucose syrup, and concentrated syrup; Step 1) The neutral acid catalyst is one or more of concentrated sulfuric acid, concentrated hydrochloric acid, phosphoric acid, citric acid, lactic acid, maleic acid, p-toluenesulfonic acid, formic acid, acetic acid, and aminosulfonic acid; the co-catalyst is an active metal chloride, specifically one or more of aluminum chloride, ferric chloride, chromium chloride, sodium chloride, potassium chloride, calcium chloride, and magnesium chloride; In step 1), the organic phase is selected from one or more mixed solvents selected from dimethyl carbonate, methanol, ethanol, 4-methyl-2-pentanone, dimethyl sulfoxide, N, N-dimethylformamide, acetonitrile, tetrahydrofuran, 2-methyltetrahydrofuran, 1-butanol, 2-butanol, γ-valerolactone, and isopropanol.
3. The method for preparing a photodegradation catalyst using humus, a byproduct of sugar hydrolysis, according to claim 1, characterized in that In step 1), the mass ratio of the sugar compound to the mass of the acidic catalyst, the mass of the co-catalyst, the volume of water, and the volume ratio of the organic solvent is 1: 0.01-0.1: 0.01-0.05: 0.2-0.8: 1.0-2.0, the volume unit is mL, and the mass unit is g; in step 1), the reaction temperature is 140-160° C., and the reaction time is 1-2 h.
4. The method for preparing a photodegradation catalyst using humus, a byproduct of sugar hydrolysis, according to claim 1, characterized in that In step 2), the metal compound is selected from one or more of TiO2, CuO, Cu2O, ZnO, Ag2O, Fe3O4, WO3, CeO2 and CdO; the non-metallic oxide is SiO2; and the organic solvent in step 2) is methanol, ethanol, isopropanol or acetone.
5. The method for preparing a photodegradation catalyst using humus, a byproduct of sugar hydrolysis, according to claim 1, characterized in that Step 2) The reaction temperature is 150-220° C. and the reaction time is 2.5-5.5 hours. In step 2), the mass ratio of the crude humins carrier to the compound is 1:2-4.
6. A photodegradation catalyst prepared by the method of claim 1.
7. Use of the photodegradation catalyst according to claim 6 in the degradation of organic dyes.
8. The use according to claim 7, characterized in that The steps include: The prepared photodegradation catalyst and organic dye are placed in a light-transmitting conical flask for reaction, and the catalyst is evenly dispersed in the organic dye by stirring. Before irradiation, stirring is performed in the dark, and then the photodegradation reaction is irradiated under light.
9. The use according to claim 8, characterized in that The organic dye solution is one or more of methylene blue, malachite green, methyl orange, crystal violet, Congo red and rhodamine B solution; the concentration of the organic dye solution is 10-50 mg / L, the pH value is 4-6.5, the reaction temperature is 20-40° C., and the concentration of the humins-loaded photodegradation catalyst when catalyzing dye degradation is 1-50 g / L; the illumination adopts one or more of natural light, ultraviolet xenon lamp, and ultraviolet mercury lamp.
10. The use according to claim 8, characterized in that The ultraviolet wavelength is 280-380nm, and the irradiation intensity is 0.30-18W / m 2 , the illumination time is 60~300min.